2001
DOI: 10.2307/3061012
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Dynamics in Zooplankton Community Responses to Acidification: Measurement and Mechanisms

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecological Applications. Abstract.Previous studies indicate substantial va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 48 publications
1
56
0
Order By: Relevance
“…In our study, zooplankton populations oscillated strongly in all treatments, resembling naturally occurring plankton ecosystems that typically show strong population oscillations due primarily to consumer-resource dynamics (McCauley et al 1999. Previous attempts to document the role of compensatory dynamics in stabilizing community responses to environmental fluctuations (Fischer et al 2001, Vasseur et al 2005) may have underestimated the importance of community dynamics since the reduction of synchrony rather than the presence of compensation may actually provide the stabilizing mechanism (see also Huber and Gaedke 2006). 4).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…In our study, zooplankton populations oscillated strongly in all treatments, resembling naturally occurring plankton ecosystems that typically show strong population oscillations due primarily to consumer-resource dynamics (McCauley et al 1999. Previous attempts to document the role of compensatory dynamics in stabilizing community responses to environmental fluctuations (Fischer et al 2001, Vasseur et al 2005) may have underestimated the importance of community dynamics since the reduction of synchrony rather than the presence of compensation may actually provide the stabilizing mechanism (see also Huber and Gaedke 2006). 4).…”
Section: Discussionmentioning
confidence: 55%
“…4). While a number of studies (Klug et al 2000, Fischer et al 2001, Bai et al 2004, Descamps-Julien and Gonzalez 2005, Vasseur et al 2005, Huber and Gaedke 2006 suggest a role for compensatory dynamics in fluctuating environments, Gonzalez and Descamps-Julien (2004) is the only study to previously show a reduction of aggregate community variance due to compensatory interactions between species in an experimental setting. The ubiquity of synchronous oscillations in natural communities has been reasonably well documented (Houlahan et al 2007), and the largely synchronous dynamics observed in this experiment resemble the dynamics observed in natural communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, trophic interactions may promote diversity through assembly processes, as colonization by one group may facilitate the colonization of another (Grover 1994). Studies examining long-term time series across a set of lakes have often found that large-scale environmental factors like climate change, acidification, or eutrophication/re-oligotrophication may promote coherent temporal changes in a set of lakes in a landscape (Magnuson et al 1990, Fischer et al 2001, Anneville et al 2005. Studies examining long-term time series across a set of lakes have often found that large-scale environmental factors like climate change, acidification, or eutrophication/re-oligotrophication may promote coherent temporal changes in a set of lakes in a landscape (Magnuson et al 1990, Fischer et al 2001, Anneville et al 2005.…”
Section: Introductionmentioning
confidence: 99%